Indoor PM10 in university classrooms: Chemical composition and source behaviour. (15th October 2022) - Perrino, C.; Pelliccioni, A.; Tofful, L.; Canepari, S.
Abstract: The indoor atmosphere of five university environments, ranging from a research laboratory to a vast lecture hall, was studied during a seven-week measurement campaign. The study was carried out in real-world conditions and was designed to distinguish periods when the environments were occupied from periods when they were empty. A comprehensive chemical characterisation of PM10 was carried out (elements as total, extractable and residual fractions, ions, elemental carbon, organic carbon), which allowed the study of the main PM sources (soil, sea, secondary inorganic species, traffic emission, organics). Other sources (heavy oil combustion, biomass burning and non-exhausts traffic emission) were well traced by the extractable or residual fractions of some elements (V, Rb, Mo). During classes, indoor PM10 concentration exceeded outdoor values. The main differences between indoor and outdoor chemical composition were due to soil components and to the organics. Soil particles were carried in by the students and re-suspended by their movements. The organics were mainly due to bioparticles released by the occupants. An increase inside classrooms was also observed for sulphate and attributed to the used of mineral gypsum as blackboard chalk. Sea-salt particles and ammonium nitrate, instead, showed a sharp decrease when entering the indoor environments, due to their large size and a shift in its thermodynamic equilibrium, respectively. The concentration of particles released by anthropogenic combustion sources (exhaust and non-exhaust traffic emission, domestic heating) was generally lower than outdoors, and the degree of their infiltration was determined by their dimensions. Graphical abstract: Image 1 Highlights: PM10 was determined in five university environments in real-world conditions. The main sources of PM and their ability to infiltrate were studied. The chemical composition of indoor and outdoor PM10 was very different. During classes, indoor PM10 concentration was higher than outdoors. Indoor concentration increase was due to soil components and to organic species.